Hair loss severity and its impact on quality of life in patients suffering from androgenic alopecia: A one-year cross-sectional study - Kriti Lohia; Bhavana Ravindra Doshi; B S Manjunathswamy (Wolters Kluwer Medknow Publications, 2021)
Background: Androgenic alopecia (AGA) is a common form of nonscarring alopecia encountered in daily dermatology practice. Both apparent and imperceptible AGA has a significant impact on an individual's personality, where physical appearance plays an important role in the probable prospects for marriage as well as other social aspects. Hair loss, thus, can severely hamper them for both men and women with clinical severity of alopecia not necessarily correlating with the quality of life (QoL) of the patient. Objectives: The objective is to assess the QoL in patients with AGA attending a tertiary care hospital in western India and compare QoL with hair loss severity (HLS), rated by both dermatologist and patient. Materials and Methods: One hundred and four patients, clinically diagnosed with AGA, consenting for the study over a period of 1 year were included. Demographic data of the patients were recorded. QoL was assessed using skindex-16 questionnaire; HLS was assessed through self-administered questionnaires completed by patients and dermatologists. Data were analyzed using Wilcoxon signed-rank test, Kendall's tau correlation coefficients, and Chi-square test. Results: The mean global score of Skindex-16 was 45.75 ± 16.90, with highest scores from emotions (64.93 ± 23.26). A positive correlation was found between the patients' HLS rating (r = 0.33, P < 0.0001) and the clinical HLS rating. However, patient rated the extent of their hair loss as more severe than the dermatologist. Patient-related HLS significantly correlated with the mean global score of Skindex-16 (P < 0.0001) as well as with all the subdomain scores (P < 0.0001), whereas dermatologist-rated HLS only significantly correlated with the global score of Skindex-16 (P = 0.04) but not with the subdomain scores. Limitations: As Skindex-16 is a self-reported questionnaire, there may be a recall bias. Another limitation of our study is the sample size; a study with a bigger sample size is required to vindicate our findings. Conclusion: The study demonstrates that AGA patients perceived their HLS as more severe than the dermatologist. Both patient-related HLS and dermatologist-rated HLS showed statistical correlation with the total global Skindex-16 score. Hence, dermatologists need to be more alert and should address the psychosocial and QOL issues, when treating patients with AGA.